Plasma coatings made of mechanically synthesized composite powders based on the «iron-aluminum» system - F. G. Lovshenko; A. S. Fedosenko (Литьë и металлургия)
The regularities of the formation of plasma coatings obtained from powders based on the Fe-Al system synthesized by the reaction mechanical alloying method are established. The influence of the processing modes of the compositions in the mechanoreactor on the properties of coatings is revealed. An effective method for controlling the porosity of coatings from developed powders based on a change in the power consumed by the installation is proposed.Plasma coatings have a nonequilibrium phase composition, which, in contrast to the equilibrium one, contains a wide range of metal oxides of the base and alloying elements formed during the spraying. The coating retains submicra – microcrystalline type of structure of powders with a highly developed grain and subgrain boundary. The basis of the coating is intermetallic FeAl. The role of hardening phases is played by ultrafine compounds of intermetallics and oxides.Powder annealing has a significant effect on the structure and properties of coatings and, first of all, on layers from compositions with complex alloying with oxides. Heat treatment increases the density and hardness of coatings and reduces porosity. The study of coating samples after high temperature indicates high heat resistance and the preservation of the microcrystalline type of structure of their bases.